Individual Education Plans and Teams: Principals’ Roles and Responsibilities - Rutherford, Emily N.; Brown, Rachel (Journal of the American Academy of Special Education Professionals, 2021)
The demand of providing adequate services for students with disabilities has evolved over the years requiring districts to provide free and appropriate public education in the least restrictive environment. As districts are held increasingly accountable for meeting these demands, the roles and responsibilities of the school principal has become greater. However, the roles and responsibilities of public school principals in the development of the individualized education plan (IEP) remain unclear. In this study, public school principals were interviewed to determine the role principals play in the IEP process and supports provided by districts to assist principals in being an effective leader in special education on their campuses. Results of the surveys are reported and implications for current practice are discussed.